L’Ecole de la rhapsodie - Claudon, Francis (Verbum – Analecta Neolatina, 2002)
In occasion of the bicentenaire of Victor Hugo’s birth the author reminds the fact that the Hungarian composer Ferenc Liszt was probably the first to contribute to Hugo’s international career by publishing six of his poems set to music in 1844. Further on he investigates about affininities and the relationships of the two personalities.